Pengendalian Hama Penggerek Buah Kopi (PBKo) bagi Kelompok Tani Sejahtera Desa Kayumas Kecamatan Arjasa Kabupaten Situbondo: Coffee Fruit Burder (PBKo) Pest Control for Prosper Farmer Group Kayumas Village, Arjasa District, Situbondo Regency - Puryantoro Puryantoro; Sasmita Sari; Firman Jaya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Coffee berry borer (PBKo) attacks can cause 50-90% crop loss for farmers. This PBKo pest is very detrimental because it can reproduce very quickly in large numbers. Partners of the service activities of the Prosperous Farmers Group, Kayumas Village, Arjasa District, Situbondo Regency. The purpose of this service is to control pests on coffee plants using PBKo pest trap technology. The implementation method begins with coordination with farmer groups and preparation of tools and materials until the implementation of pest traps on farmer group lands through counseling and direct practice on farmers' land for three months. Farmers' enthusiasm for this activity is outstanding, considering that in the long-term eradication of PBKo pests using this trap is a solution to increase coffee production in the coming season. After the service activities were carried out, there was an increase in the skills and knowledge of partners using PBKo pest traps using coptans and pheromones so that it would reduce the population of fruit borer pests on farmers' coffee plants.